A co-production study of an art-based media campaign intervention to encourage early breast cancer screening uptake among Black women in England - Tarela Juliet Ike; Dung Ezekiel Jidong; Mieyebi Lawrence Ike; Evangelyn Ebi Ayobi; Peremi Richmond Ike; Oluwakorede Florence Adebowale; Gabriella Rooks; Nusrat Husain (Frontiers in Public Health, 2026)
Background Breast cancer is one of the most common cancers that affects women globally. Of central concern are Black women in the United Kingdom who are disproportionately affected, present late and suffer higher mortality due to poor early screening uptake. Informed by an interpretative phenomenological analytical lens, this study makes an original and significant contribution to address the gap by working with 15 Black women from the north of England to co-produce an art-based media campaign intervention designed to encourage early breast cancer screening uptake. Method N = 10 participants took part in a focus group discussion, while N = 5 took part in individual interviews. Data were analyzed using interpretative phenomenological analysis. Findings The following main themes emerged: (i) Uncertainty underpinned by poor awareness, (ii) Fear of the unknown, (iii) From fear to action: Empowerment-focused breast screening communication, (iv) Animated content, (v) Embedding awareness in women’s everyday digital spaces, and (vi) Empowerment through coproduction, inclusive voice and agency. Conclusion The study has important policy implications, including the need for co-designed interventions to foster uptake, and it also recommends testing the co-produced intervention to determine its feasibility, effectiveness, and cost-effectiveness in encouraging early screening uptake among this marginalized population.